The long non-coding RNA HOTAIR is transcriptionally activated by HOXA9 and is an independent prognostic marker in patients with malignant glioma - Xavier-Magalhães, Ana (2018)
The lncRNA HOTAIR has been implicated in several human cancers. Here, we evaluated the molecular alterations and upstream regulatory mechanisms of HOTAIR in glioma, the most common primary brain tumors, and its clinical relevance. HOTAIR gene expression, methylation, copy-number and prognostic value were investigated in human gliomas integrating data from online datasets and our cohorts. High levels of HOTAIR were associated with higher grades of glioma, particularly IDH wild-type cases. Mechanistically, HOTAIR was overexpressed in a gene dosage-independent manner, while DNA methylation levels of particular CpGs in HOTAIR locus were associated with HOTAIR expression levels in GBM clinical specimens and cell lines. Concordantly, the demethylating agent 5-Aza-2'-deoxycytidine affected HOTAIR transcriptional levels in a cell line-dependent manner. Importantly, HOTAIR was frequently co-expressed with HOXA9 in high-grade gliomas from TCGA, Oncomine, and our Portuguese and French datasets. Integrated in silico analyses, chromatin immunoprecipitation, and qPCR data showed that HOXA9 binds directly to the promoter of HOTAIR. Clinically, GBM patients with high HOTAIR expression had a significantly reduced overall survival, independently of other prognostic variables. In summary, this work reveals HOXA9 as a novel direct regulator of HOTAIR, and establishes HOTAIR as an independent prognostic marker, providing new therapeutic opportunities to treat this highly aggressive cancer.